2009
DOI: 10.1186/1743-0003-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Technology-assisted training of arm-hand skills in stroke: concepts on reacquisition of motor control and therapist guidelines for rehabilitation technology design

Abstract: Background: It is the purpose of this article to identify and review criteria that rehabilitation technology should meet in order to offer arm-hand training to stroke patients, based on recent principles of motor learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
290
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(296 citation statements)
references
References 154 publications
(213 reference statements)
4
290
0
2
Order By: Relevance
“…5 Regarding training physiology, a goal-dependent functional and specific skill training was offered with training loads exceeding the patient's metabolic capacity (overload principle 4 ). As to motor learning principles, 'over-learning strategies' (that is, continued practice after performance), 'exercise variability' to improve patient's motivation and conserve training effect and 'guidance and feedback' 5,9 (provided by the haptic robot device 8,11 ) were used. Patients were offered a task-oriented training, that is, a repetitive training of self-selected, real life activities, to also improve their motivation.…”
Section: Materials and Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Regarding training physiology, a goal-dependent functional and specific skill training was offered with training loads exceeding the patient's metabolic capacity (overload principle 4 ). As to motor learning principles, 'over-learning strategies' (that is, continued practice after performance), 'exercise variability' to improve patient's motivation and conserve training effect and 'guidance and feedback' 5,9 (provided by the haptic robot device 8,11 ) were used. Patients were offered a task-oriented training, that is, a repetitive training of self-selected, real life activities, to also improve their motivation.…”
Section: Materials and Interventionmentioning
confidence: 99%
“…All skills were broken down into subskills or components. 9,11 For each of these components, exercises were offered at increasing levels of difficulty with the feedback delivered according to the shaping principles. 12 Exercise progression was based on principles of training physiology 4 and motor learning.…”
Section: Materials and Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors are thought to enhance plasticity-based rehabilitation, such as task-oriented movement practice in a challenging, engaging, functional, and meaningful way, and the rehabilitation should address body function and structures, activity, and participation level [9][10][11][12][13]15]. Rehabilitation has shown that, even in chronic stroke, improved upperlimb outcomes can be achieved [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Motor (re)learning and recovery are mainly possible because of plasticity of the brain [7], and the changes caused by plasticity in the lesioned hemisphere coincide with motor function improvement after activity-based rehabilitation [3]. In addition to neural plasticity changes in the lesioned side, motor recovery may occur because of a shift of balance in the motor cortical recruitment toward the undamaged hemisphere via the ipsilateral pathways [8][9].…”
Section: Introductionmentioning
confidence: 99%